2017
DOI: 10.1088/1741-4326/aa7db0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neutral density fluctuations on gas puff imaging diagnostics

Abstract: A three-dimensional turbulence simulation of the SOL and edge regions of a toroidally limited tokamak is carried out. The simulation couples self-consistently the drift-reduced two-fluid Braginskii equations to a kinetic equation for neutral atoms. A diagnostic neutral gas puff on the low-field side midplane is included and the impact of neutral density fluctuations on light emission investigated. We find that neutral density fluctuations affect the emission. In particular, at a radial distance from the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…It is found that densities of thermal molecules and atoms which do not originate from dissociative processes behave as reported in [7,8], i.e., the neutral density decreases locally due to interactions with the electrons in the filament. The density of atoms from dissociated molecules, however, displays an opposite behaviour if the reaction rate for dissociation of molecules is bigger than that for ionization of atoms, which is the case in the SOL region for the results presented here.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is found that densities of thermal molecules and atoms which do not originate from dissociative processes behave as reported in [7,8], i.e., the neutral density decreases locally due to interactions with the electrons in the filament. The density of atoms from dissociated molecules, however, displays an opposite behaviour if the reaction rate for dissociation of molecules is bigger than that for ionization of atoms, which is the case in the SOL region for the results presented here.…”
Section: Introductionmentioning
confidence: 52%
“…is always negative, resulting in the anti-correlation between the atom density and the electron density as observed in [7,8]. For the source of deuterium atoms in (5), however, the sign is determined by the ratio of the absolute value of the two terms…”
Section: Correlated Perturbations In the Scrape-off Layermentioning
confidence: 97%
See 1 more Smart Citation
“…The PDF of these signals furthermore are close to a normal distribution, with low moments of skewness, excess kurtosis and no elevated tails. It is plausible that ionization, where hot plasma filaments locally decrease the puffed gas density, is the main cause of this phenomenon and therefore should be accounted for in such an attempt to reproduce the emission from measurements of n e and T e (Thrysøe et al 2016;Wersal & Ricci 2017).…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…In the 1D model, turbulence structures interact with neutrals through poloidal (y) averages, i.e., the neutrals "average over" the turbulence by virtue of their relatively long MFPs. For example, the neutral shadow [25] cast by a plasma blob may show up as a negative fluctuation in the radial neutral density profile, provided the blob shows up in the SOL plasma profile. This admittedly limited description may suffice for modeling the self-consistent evolution of neutral and plasma profiles.…”
Section: Introductionmentioning
confidence: 99%